2022
DOI: 10.1186/s12967-022-03499-0
|View full text |Cite
|
Sign up to set email alerts
|

Low potassium disrupt intestinal barrier and result in bacterial translocation

Abstract: Background Bacterial translocation was observed in critical illness and patients with chronic diseases such as liver cirrhosis and chronic kidney disease (CKD). Hypokalemia is a common complication in these diseases. Whether low potassium diet may increase intestinal permeability and result in bacterial translocation lack of evidence. The present study was aimed to investigate the potential effects of LK on intestinal permeability. Methods Grade 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In our cohort, the PD patients showed a smaller intake of potassium compared with healthy controls, which, based on other studies, may be related to the impaired intestinal barrier and may alter the cellular signaling in the basal ganglia. Recently, a study of mice reported that a low potassium diet could increase intestinal permeability, which may result in bacterial translocation [ 102 ]. Additionally, changes in potassium could influence the regulation of K(+) channels and are important for cellular signaling in the basal ganglia; therefore, impairments in potassium could also have a relation with PD disease [ 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, the PD patients showed a smaller intake of potassium compared with healthy controls, which, based on other studies, may be related to the impaired intestinal barrier and may alter the cellular signaling in the basal ganglia. Recently, a study of mice reported that a low potassium diet could increase intestinal permeability, which may result in bacterial translocation [ 102 ]. Additionally, changes in potassium could influence the regulation of K(+) channels and are important for cellular signaling in the basal ganglia; therefore, impairments in potassium could also have a relation with PD disease [ 103 , 104 , 105 ].…”
Section: Discussionmentioning
confidence: 99%